1993
DOI: 10.1346/ccmn.1993.0410403
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Paragenesis of Na-Beidellite as a Function of Temperature, Water Pressure, and Sodium Activity

Abstract: Abstract--In the chemical system NayO-AIyO3-SiO2-HyO, the stability field of Na-beidellite is presented as a function of pressure, temperature, and Na-and Si-activity. NaoT-beidellite was hydrothermally synthesized using a stoichiometric gel composition in the temperature range from 275* to 475~ and at pressures from 0.2 to 5 kbar. Below 275~ kaolinite was the only crystalline phase, and above about 500~ paragonite and quartz developed instead of beidellite. An optimum yield of 95% of the Nao.7-beidellite was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 27 publications
(33 reference statements)
5
19
2
Order By: Relevance
“…At temperatures below 175~ mainly amorphous material, kaolinite, or zeolites (at lowest gel/solution ratio) were formed (Figure 3). These results represent the lowest pressure and temperature conditions under which beidellite formation has been reported and differ from those of other authors, such as Kloprogge et al (1993b), who found a minimum temperature of 200~ to yield beidellite + amorphous material.…”
Section: Beidellitecontrasting
confidence: 98%
See 4 more Smart Citations
“…At temperatures below 175~ mainly amorphous material, kaolinite, or zeolites (at lowest gel/solution ratio) were formed (Figure 3). These results represent the lowest pressure and temperature conditions under which beidellite formation has been reported and differ from those of other authors, such as Kloprogge et al (1993b), who found a minimum temperature of 200~ to yield beidellite + amorphous material.…”
Section: Beidellitecontrasting
confidence: 98%
“…Kloprogge et al (1993b) also observed this mixed-layer phase in their products synthesized at 2 kbar and higher. Additional experiments (Nakazawa et al, 1992) showed that at 450~ cristobalite also formed, and at 475~ both cristobalite and quartz were present, in agreement with the data of Kloprogge et aL (1993b).…”
Section: Compositional Seriesmentioning
confidence: 76%
See 3 more Smart Citations